(untitled) (Palimpsesto, 2022)
This reflective essay addresses the role of crises in contemporary societies by examining the type of social experience they generate. Building on the work of the German philosopher Rahel Jaeggi, we will develop her theory of crises as blockages of the dynamics of social learning in life forms understood as networks of practices oriented to problem solving. The concept "modes de vie" developed by the Belgian philosopher Mark Hunyadi, serves as a complement to account for the predominance of a sense of crises as systemic collapses and the change in their character towards a social disciplining device that subtracts from social capacities of reflection and ethical-political transformation.